Costs of Timber Houses in Different Standards and Productions in Brazil - Araujo, Victor Almeida de; Araujo, Francisco Vasconcelos de; Vasconcelos, Juliano Souza [UNESP]; Gava, Maristela [UNESP]; Christoforo, Andre Luis; Garcia, Jose Nivaldo (Univ Distrital Francisco Jose De Caldas, Centro Invest & Desarrollo Cient, 2023)
Context: Timber construction is not among the most popular options due to cultural issues in Brazil. Timber housing standards and costs remain uncertain subjects, and this study seeks to investigate these secular gaps.Method: Basic unitary costs for different finishing standards and production types were measured through face-to-face interviews led by a semi-structured questionnaire. A margin of error was used to validate all re-sults. Entrepreneurs from six Brazilian states were randomly interviewed to obtain a representative sample.Results: The sampling exceeded 50% of the sector population and provided significant outcomes. More than 40% of timber housing techniques showed competitive costs in comparison with masonry. There are feasible alternatives of timber housing for the different scenarios analyzed.Conclusions: Timber houses are economically viable in Brazil, even compared to traditional examples built via masonry. Attractive costs for all social classes symbolize a strong factor in conquering housing markets.
Keywords: construction; housing; timber industry; building standard; cost; interview